Additive and non-additive epigenetic signatures of natural hybridization between fish species with different mating systems. Issue 13 (9th December 2022) - Berbel-Filho, Waldir M.; Pacheco, George; Lira, Mateus G.; Garcia de Leaniz, Carlos; Lima, Sergio M. Q.; Rodríguez-López, Carlos M.; Zhou, Jia; Consuegra, Sofia
ABSTRACT: Hybridization is a major source of evolutionary innovation. In plants, epigenetic mechanisms can help to stabilize hybrid genomes and contribute to reproductive isolation, but the relationship between genetic and epigenetic changes in animal hybrids is unclear. We analysed the relationship between genetic background and methylation patterns in natural hybrids of two genetically divergent fish species with different mating systems, Kryptolebias hermaphroditus (self-fertilizing) and K. ocellatus (outcrossing). Co-existing parental species displayed highly distinct genetic (SNPs) and methylation patterns (37, 000 differentially methylated cytosines). Hybrids had predominantly intermediate methylation patterns (88.5% of the sites) suggesting additive effects, as expected from hybridization between genetically distant species. The large number of differentially methylated cytosines between hybrids and parental species (n = 5, 800) suggests that hybridization may play a role in increasing genetic and epigenetic variation. Although most of the observed epigenetic variation was additive and had a strong genetic component, we also found a small percentage of non-additive, potentially stochastic, methylation differences that might act as an evolutionary bet-hedging strategy and increase fitness under environmental instability.